(untitled) (Medico Legal Update, 2020)
The current study was carried out during the period between November/2018 and March/2019. The study was aiming to investigate the types and proportions of intestinal parasites among children who visited the primary health care center in the city of Khanaqin - Diyala governorate. The total number of specimens examined, during the course of study, was 805 stool specimens. These specimens were taken from children in the age range 1-10 years, and direct smear was the method used for the investigation of the intestinal parasites existence. The results showed that 156 children were infected with intestinal parasitic infections. These infections were categorized as four types of Protozoa and one type of intestinal Helminthes. The incidence ratio of intestinal parasitic infection was 19.373%, where the percentages of parasites considered in the current study have found to be 62.179% for the Entamoebahistolytica followed by 12.820% for the Giardia lamblia, 12.820 of Entamoebacoli, and 3.205% for the Iodomoebabutschillii. Moreover, the study has reported one type of Helminthes represented by the Entrobiusvermicularis with occurrence ratio of 6.410%.